Intergalactic propagation of ultrahigh energy cosmic ray nuclei: An analytic approach - Hooper, D; Sarkar, S; Taylor, A (2008)
It is likely that ultrahigh energy cosmic rays contain a significant component of heavy or intermediate mass nuclei. The propagation of ultrahigh energy nuclei through cosmic radiation backgrounds is more complicated than that of protons and its study has required the use of Monte Carlo techniques. We present an analytic method for calculating the spectrum and the composition at Earth of ultrahigh energy cosmic rays which start out as heavy nuclei from their extragalactic sources. The results obtained are in good agreement with those obtained using numerical methods. © 2008 The American Physical Society.